2016
DOI: 10.1063/1.4942635
|View full text |Cite
|
Sign up to set email alerts
|

Materials design for electrocatalytic carbon capture

Abstract: We discuss our philosophy for implementation of the Materials Genome Initiative through an integrated materials design strategy, exemplified here in the context of electrocatalytic capture and separation of CO2 gas. We identify for a group of 1:1 X–N graphene analogue materials that electro-responsive switchable CO2 binding behavior correlates with a change in the preferred binding site from N to the adjacent X atom as negative charge is introduced into the system. A reconsideration of conductive N-doped graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…We investigated the relationship of the different boxes ( a × b × c , a = b , c = 40 Å) of the graphene cell and energy (Figure S1). We finally adopted a unit cell of parameters a = 17.06 Å, b = 17.06 Å, and c = 40 Å composed of 112 carbon atoms in subsequent calculations . On the basis of the unit cell of this nondefective graphene sheet, two different types of N-doped graphene surfaces were constructed.…”
Section: Computational Methods and Detailsmentioning
confidence: 99%
“…We investigated the relationship of the different boxes ( a × b × c , a = b , c = 40 Å) of the graphene cell and energy (Figure S1). We finally adopted a unit cell of parameters a = 17.06 Å, b = 17.06 Å, and c = 40 Å composed of 112 carbon atoms in subsequent calculations . On the basis of the unit cell of this nondefective graphene sheet, two different types of N-doped graphene surfaces were constructed.…”
Section: Computational Methods and Detailsmentioning
confidence: 99%
“…The idea can be well applied and generalized to other 2D materials like electron charged graphitic carbon nitrides (C 3 N 4 ) and N-doped graphene, both of which have been proposed for the CO 2 capture (Tan, Kou, Tahini, & Smith, 2015;Tan, Tahini, & Smith, 2016b), where the charged nitrogen as the active capturing sites. Most of the cases, gas sensing materials can be also used for gap capture if the adsorption strength is strong enough due to the same mechanism, namely electron transfer.…”
Section: Two-dimensional Materials For Gas Capturementioning
confidence: 99%
“…found that borophene achieved a CO 2 capacity of 6.73×10 14 molecules per cm −2 with a charge density of 57.2×10 13 e − cm −2 , and the desorption of CO 2 was exothermic by 1.99 eV when rejecting charges [18] . They also reported that the CO 2 adsorption energy increased from 0.17 to 0.58 eV when 4 e − was injected into N‐doped graphene [19] . Carbon nitrides such as C 2 N and C 3 N have also been demonstrated as efficient charge‐modulated CO 2 capture and separation materials [20,21] .…”
Section: Introductionmentioning
confidence: 96%